2017
DOI: 10.1590/1981-6723.8315
|View full text |Cite
|
Sign up to set email alerts
|

Produção e estabilidade de conservação de farinha de acerola desidratada em diferentes temperaturas

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Produção e estabilidade de conservação de farinha de acerola desidratada em diferentes temperaturas Production and storage stability of acerola flour dehydrated at different temperatures ResumoO objetivo deste trabalho foi identificar a melhor temperatura de desidratação para a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
6
5
0
5
Order By: Relevance
“…The green banana flour presented final moisture (6.47%) close to the values of the present study, stored in PET packaging for 90 days, at room temperature of ±26 ° C, in the study conducted by Santos et al (2010). Reis et al (2017) determined high humidity values between 18.78% and 25.48% for acerola meal (differentiated by the presence or absence of the seed in its composition) stored for 75 days in PET packages.…”
Section: Resultssupporting
confidence: 86%
“…The green banana flour presented final moisture (6.47%) close to the values of the present study, stored in PET packaging for 90 days, at room temperature of ±26 ° C, in the study conducted by Santos et al (2010). Reis et al (2017) determined high humidity values between 18.78% and 25.48% for acerola meal (differentiated by the presence or absence of the seed in its composition) stored for 75 days in PET packages.…”
Section: Resultssupporting
confidence: 86%
“…Factors such as the applied dehydration method, storage time and packaging used directly influence the oxidation reactions to which the product is susceptible. Reis et al (2017) observed an increase in the concentration of vitamin C after dehydration of acerola cherry. The same authors also found that the final concentration of this vitamin was lower when they used lower temperatures and longer periods of time, since the longer exposure time in drying degrades the nutritional constituents of food.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 93%
“…Chroma values define color intensity, where values close to zero correspond to neutral colors, and values close to sixty account for stronger colors (Tunick, 2000). Chroma is a variable related to the degree of purity of the color, which delimits the saturation level by the black or white scale that contains it (Reis et al, 2017).…”
Section: Increase In Browning Chroma and Hue Anglementioning
confidence: 99%